Artificial Intelligence and Agritourism Development: Mixed Feelings on Digital and Social Media Marketing in Africa - Mashapure, Rahabhi; Tapera, Julius; Hamunakwadi, Purity; Mtombeni, Admire; Mutanda, Bronson; Chikazhe, Lovemore (Indonesian Journal of Community Services, 2025)
The emergence of artificial intelligence and its progressively wider impact on many sectors requires an assessment of its effect on the achievement of the Sustainable Development Goals. Artificial intelligence has been advancing rapidly in recent years, measured both in terms of the quantity of resources devoted to it and also in terms of its outputs. Artificial intelligence is increasingly reshaping businesses by performing various tasks, constituting a major source of innovation, yet threatening human jobs. The article reviews recent research in this area that suggests that AI and robotics have the potential to increase productivity and growth of agritourism, but may have mixed effects on labor, particularly in the short run. Using the positivism research philosophy, the study also sought to examine the insights, attitudes, and involvements of participants toward AI-driven marketing technologies in agritourism. Further, it assessed the socio-cultural, economic, and environmental influences of digital and social media marketing on African agritourism destinations. It also sought to ascertain paramount practices, challenges, and opportunities for leveraging AI technologies to stimulate sustainable agritourism development in Africa. The study considered current and potential policies around AI that could potentially help boost agritourism development while also mitigating any labor market downsides, including evaluating the pros and cons of AI on African agritourism development. The study finds that organizational factors, positive socio-cultural factors, economic factors, and environmental factors play a crucial role in the adoption of artificial intelligence by agritourism industries. Based on the study findings, the paper recommended that the fast adoption of AI needs to be supported by the necessary regulatory insight and oversight for AI-based technologies to enable agritourism sustainable development. Failure to do so could result in gaps in transparency, safety, and ethical standards. The findings also informed recommendations for further study and guided the discourse on implications for policy and practice, which other researchers, policymakers, and practitioners could potentially draw learning points from.